Marketing Strategy of Cayenne Pepper Commodities in Supporting the Policies of the Badung Regency Government - I Gusti Nyoman Wijayana; Ida Bagus Komang Mahardika; I Gusti Bagus Udayana; Yohanes Parlindungan Situmeang; I Gusti Agus Maha Putra Sanjaya; Desak Ketut Tristiana Sukmadewi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study analyzes the marketing strategies for cayenne pepper in Badung Regency, Bali, to support government policies aimed at enhancing horticultural competitiveness and farmer welfare. Conducted in the production centers of Mengwi, Abiansemal, and Petang, the research utilized a mixed-methods approach incorporating Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and Internal-External (IE) matrices, followed by a SWOT analysis. The results position the cayenne pepper agroindustry in Quadrant I (Strength–Opportunity), signifying robust internal capabilities and significant market potential. With an IFE score of 2.820 and an EFE score of 2.870, the study identifies high product quality and rising market demand as primary drivers, while production fluctuations and price uncertainty remain key challenges. To optimize this potential, the study recommends a multi-faceted strategy: stabilizing production through strengthened farmer groups, launching chili subscription programs for culinary businesses, and utilizing digital platforms. Furthermore, establishing weekly farmers' markets, fostering partnerships with supermarkets, and diversifying processed products are essential to stabilizing supply and improving the economic welfare of local farmers. Contribution to Sustainable Development Goals (SDGs):SDG 6 – Clean Water and Sanitation: SDG 11 – Sustainable Cities and Communities: SDG 13 – Climate Action: SDG 15 – Life on Land